Vai trò của FDI và đặc trưng doanh nghiệp đối với xuất khẩu của các doanh nghiệp Việt Nam - Phạm Thế, Anh; Nguyễn Trọng, Hoài (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
This research examines the role of FDI in promoting the export capacity of Vietnamese firms, using a panel of nearly 140,000 observations during the 2011–2013 period. Adopting Heckman model helps control for the sample selection bias and estimate simultaneously two decisions of export participation and intensity. The estimation results suggest that FDI exerts a significant impact on the export capacity of domestic firms or export spillovers do exist. Domestic firms of private ownership with longer establishment duration, higher capital intensity, and locations in the north and central regions benefit from export spillovers. Key policy recommendations are directed towards supporting the private sector.
Keywords: FDI; Chế biến chế tạo; Determinants; Manufacturing